L'elevage des ovins et des caprins dans le sud-est du Nigeria - Francis, P.A. (1988)
Relates livestock management systems to characteristic problems facing small ruminant producers in the physical and economic environment of four states of southeast Nigeria, viz, Bendel Anambra, Imo and Rivers states. Assesses the implications of increasing population density and intensified agriculture for smallholder livestock production systems throughout the zone.